Simulated stone ceramic tile and preparation method thereof

By setting up inkjet printed layers and optimizing the chemical composition of dry grain layer and the graphics layer in the simulated stone tiles, the problem of the existing technologies with unsuccessful and poor texture effects of simulation stone tiles, long -term anti -slip, and achieved long -acting non -slip and non -slip. Institute of anti -pollution, easy cleaning and three -dimensional effects.

CN119350067AActive Publication Date: 2025-01-24GUANGDONG NEWPEARL CERAMIC GRP CO LTD +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411498738.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-24
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

When existing simulated stone tiles achieve anti-slip effects, molds or chemical anti-slip agents are often used, resulting in poor product texture effect, easy to hide dirt and lack of anti-slip properties. At the same time, the dry grain layer accumulation effect prepared by traditional processes is poor, resulting in unclear and non-three-dimensional texture effect.

Method used

By adjusting the interlayer structure of the simulated stone tiles, setting up inkjet printing layers above and below the dry particle layer, and using a special chemical composition of the dry particle layer and surface glaze layer to ensure that the product can be realized without the use of molds or chemical anti-slip agents. Long-lasting anti-slip, anti-stain and easy to clean. At the same time, the silicon-aluminum ratio and sodium-potassium content of the dry particle layer are optimized, and pinhole defects and particle size are controlled to improve texture clarity and three-dimensional effects.

Benefits of technology

It achieves the long-term anti-slip, anti-fouling and easy-to-clean effects of simulated stone tiles without introducing molds or chemical anti-slip agents. It also improves the texture clarity and three-dimensional effect of the product, avoiding the cumbersomeness and structure of post-processing. damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005101969710000091
    Figure BDA0005101969710000091
  • Figure BDA0005101969710000092
    Figure BDA0005101969710000092
  • Figure BDA0005101969710000101
    Figure BDA0005101969710000101
Patent Text Reader

Abstract

The invention discloses a simulated stone ceramic tile and a preparation method thereof, and belongs to the field of ceramics. The simulated stone ceramic tile comprises a surface glaze layer, a first ink-jet printing layer, a dry particle layer and a second ink-jet printing layer which are adjacent in sequence, the surface glaze layer comprises the following chemical components in specific percentage content: Al2O3, SiO2, K2O, Na2O, CaO, ZrO2, MgO, ZnO and BaO; the dry particle layer is prepared from the following chemical components in percentage by mass: Al2O3, SiO2, K2O, Na2O, CaO, SrO, MgO, ZnO and BaO. The product not only can realize long-acting skid resistance under the condition of not introducing a mold or a chemical anti-skid agent, but also is not easy to hide dirt, can realize good color development and definition without later processing, and is good in simulation three-dimensional effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to a simulated stone tile and a preparation method thereof. Background Art

[0002] Simulated stone tiles are favored by the market for their three-dimensional simulated stone tile surface effect. They are generally made of dry particles with inkjet patterns to achieve the required simulated texture and feel. In order to achieve the anti-slip effect, this type of product generally increases the roughness of the tile surface through molds or adjusts the layer material formula, or adds chemical anti-slip agents to the tile surface to make it adsorb on the tile surface to increase the friction coefficient. However, in addition to affecting the texture effect of the tile, the former will also make the product easy to hide dirt and difficult to clean, while the chemical anti-slip agents used in the latter may be harmful to the human body. After a period of use, they are easy to lose their effect due to volatilization, shedding, chemical reactions and other factors, and the anti-slip property is not durable.

[0003] On the other hand, after the current simulated stone tiles are prepared through traditional processes, some of the accumulated dry particles in the dry particle layer have low transparency and poor stacking and positioning effect, which makes the color and clarity of the overall texture and pattern effects poor. Further post-processing is required, otherwise the three-dimensional effect is poor and the sense of simulation cannot be achieved. Post-processing is not only cumbersome, but may also destroy the organizational structure of the dry particle layer. Summary of the invention

[0004] Based on the defects of the prior art, the purpose of the present invention is to provide a simulated stone tile. By adjusting the interlayer structure of the product, an inkjet printing layer is arranged on the upper and lower sides of the dry particle layer, and a special chemical composition of the dry particle layer and the surface glaze layer is set, so that the product can not only achieve long-term anti-slip without introducing molds or chemical anti-slip agents, but also is not easy to hide dirt and grime and is easy to clean; the product can achieve good color and clarity without post-processing, and has a good simulated three-dimensional effect.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is:

[0006] A simulated stone tile comprises a surface glaze layer, a first inkjet printing layer, a dry particle layer and a second inkjet printing layer which are adjacent to each other in sequence;

[0007] The surface glaze layer comprises the following chemical components in percentage by mass: Al2O3 19.56-25.12%, SiO2 49.14-56.5%, K2O 2.11-3.05%, Na2O 2.89-4.05%, CaO 2.12-3.75%, ZrO2 4.54-7.65%, MgO 0.97-1.85%, ZnO 2.16-4.45%, BaO 0.19-1%;

[0008] The dry particle layer includes the following chemical components in percentage by mass: Al2O3 16.56-20.12%, SiO2 47.14-52.51%, K2O 1.31-2.61%, Na2O 3.89-5.05%, CaO 2.05-4.88%, SrO 2.54-4.65%, MgO 1.02-1.85%, ZnO 3.16-5.45%, and BaO 8.41-12.10%.

[0009] The product of the present invention is based on the technical defects of the existing dry particle type simulated stone tiles. By developing a new type of surface glaze layer and dry particle layer formula, the product can achieve long-term anti-skid, anti-fouling and easy-to-clean effects without introducing chemical anti-skid agents or molds: by adjusting the silicon-aluminum ratio and the sodium-potassium content in the dry particle layer, the melting temperature range of the dry particle layer is adjusted to improve the wear resistance of the product and increase the friction coefficient. At the same time, the content of metal oxides barium oxide, zinc oxide, calcium oxide and magnesium oxide is adjusted to control the number of pinhole defects and particle size of the dry particle layer, so that the product has both anti-fouling performance and easy cleaning performance; in addition, by introducing an appropriate amount of strontium, the gloss and transparency of the dry particle layer can be effectively controlled, and the flatness of the accumulated dry particles can be improved, which not only has better anti-fouling performance, but also has higher texture effect and clarity of the product pattern, and better three-dimensional effect. On the other hand, for the surface glaze layer that does not contain strontium, its chemical composition must also be compatible with the dry particle layer to ensure the tightness of the connection between the surface glaze layer, the first inkjet printing layer and the dry particle layer in the product, and to ensure the anti-skid performance and three-dimensional effect of the product.

[0010] In addition, when designing the interlayers of the product described in the present invention, after setting the surface glaze layer, a first inkjet printing layer is pre-set, and then the adhesion characteristics of the first inkjet printing layer are used to position and adsorb the powdered dry particles of the dry particle layer, and then the second inkjet printing layer is applied. This sandwich structure setting not only does not affect the performance of the product, but also can fix the dry particles during the firing process of the product so that they are fully integrated with the inkjet pattern. The improved dry particle layer formula solves the defects of unclear and non-three-dimensional texture effects caused by poor stacking effects of traditional dry particle layers.

[0011] Preferably, the surface glaze layer comprises the following raw materials in parts by weight: 5-15 parts of air knife clay, 5-15 parts of calcined kaolin, 15-30 parts of potassium feldspar, 15-30 parts of sodium feldspar, 5-9 parts of wollastonite, 5-15 parts of nepheline powder, 3-8 parts of calcined zinc oxide, 5-15 parts of zirconium silicate, 5-15 parts of quartz, 7-12 parts of calcined aluminum oxide, 5-10 parts of matte frit, and 3-5 parts of dolomite;

[0012] The matte frit comprises the following chemical components in percentage by mass: Al2O3 10.14-15.12%, SiO2 50.14-55.68%, K2O 4.15-5.04%, Na2O 1.04-1.85%, CaO 8.12-10.18%, ZnO 4.01-5.45%, BaO 10.56-13.16%, and B2O3 1.98-3.54%.

[0013] Preferably, the dry particle layer comprises the following raw materials in parts by weight: 15-25 parts of potassium feldspar, 35-45 parts of sodium feldspar, 5-10 parts of calcined kaolin, 8-12 parts of barium carbonate, 3-6 parts of calcined zinc oxide, 3-7 parts of strontium carbonate, 1-5 parts of quartz, 5-10 parts of dolomite, and 3-8 parts of calcined alumina.

[0014] Preferably, the dry particle layer comprises the following chemical components in percentage by mass: Al2O3 18-19%, SiO2 49.5-50.5%, K2O 1.7-1.8%, Na2O 4.1-4.5%, CaO 2-2.5%, SrO2.9-3%, MgO 1.4-1.5%, ZnO 5-5.2%, and BaO 10-10.5%.

[0015] The chemical composition of the dry particles in the dry particle layer is crucial to the long-term slip resistance and anti-fouling performance of the product. It will also affect the clarity and three-dimensional effect of the product surface texture. After optimization, the dry particle layer with the above chemical composition can be fully integrated and positioned with the inkjet printing layer during the firing process while ensuring the performance of the product, thereby further achieving better apparent visual effects.

[0016] Preferably, the simulated stone tile further comprises a body layer and an effect pattern layer arranged on the body layer.

[0017] By pre-printing the texture effect pattern on the body layer and then setting other structural layers such as the glaze layer, the higher temperature of the body layer during the firing process can fully evaporate the moisture in the effect pattern layer, making the peeling effect of the upper glaze layer better and the texture effect better.

[0018] Another object of the present invention is to provide a method for preparing the simulated stone tile, comprising the following steps:

[0019] Setting a body layer, then printing a texture effect pattern on the body layer, and setting an effect pattern layer;

[0020] A surface glaze layer is provided on the effect pattern layer;

[0021] Providing a first inkjet printing layer on the surface glaze layer by inkjet printing;

[0022] Disposing a dry particle layer on the first inkjet printing layer;

[0023] Arranging a second inkjet printing layer on the dry particle layer by inkjet printing to obtain a rough blank;

[0024] The rough blank is fired, and then polished and edge-ground to obtain the simulated stone tile.

[0025] During the preparation process of the simulated stone tile described in the present invention, an effect texture pattern is printed on the body layer in advance to set a pattern layer, and a surface glaze layer is set on the layer, so that the high heat of the body layer can be used to quickly evaporate the moisture of the pattern layer during the firing process of the product, so that the surface glaze layer is fully peeled off and the whole presents a good effect texture. Subsequently, through the sandwich setting of the first inkjet printing layer-dry particle layer-second inkjet printing layer, the dry particle layer is positioned and evenly stacked without the use of chemical glue, and is fully integrated with the inkjet pattern, so that the texture and three-dimensional effect of the product are guaranteed under the premise of achieving anti-slip and easy-to-clean performance, and an ideal simulation effect is achieved.

[0026] Preferably, the dry particle layer is provided by dispensing dry particles;

[0027] More preferably, the preparation method of the dry particles is:

[0028] The raw materials for preparing the dry particle layer are mixed, then melted at 1400-1550°C, cooled, and the obtained sintered mass is crushed and passed through a 250-300 mesh sieve to obtain dry particles.

[0029] Preferably, the glaze amount of the dry particle layer is 100-150 g / m 2 .

[0030] Preferably, the surface glaze layer is provided by applying a surface glaze slurry;

[0031] More preferably, the surface glaze is prepared by:

[0032] The raw materials for preparing each surface glaze layer are mixed, then water is added, mixed and ball-milled, and sieved to obtain the surface glaze slurry.

[0033] Preferably, the specific gravity of the surface glaze slurry is 1.88-1.92 g / mL.

[0034] More preferably, the glaze amount of the surface glaze layer is 200-300 g / m 2 .

[0035] Preferably, the firing temperature is 1150-1200° C., and the firing time is 50-80 min.

[0036] Preferably, the green body layer comprises the following raw materials in parts by weight:

[0037] 20-35 parts of potassium-sodium sand, 15-25 parts of ball clay, 10-15 parts of kaolin, 5-10 parts of bentonite, 4-10 parts of talc, 15-25 parts of potassium-sodium water abrasive, 3-5 parts of pyrophyllite, and 2-5 parts of diopside.

[0038] It should be noted that the dry particle layer of the present invention inevitably includes impurities and loss on ignition, and the impurities and loss on ignition are generally not higher than 10%.

[0039] Preferably, the texture effect pattern is realized by printing pattern ink, and the printing amount is 3-8g / m 2 .

[0040] Preferably, the inkjet printing amount of the first inkjet printing layer and the second inkjet printing layer is 1 to 5 g / m 2 The grayscale of the first inkjet printing layer and the second inkjet printing layer is 15-40%.

[0041] The beneficial effect of the present invention is that the present invention provides a simulated stone tile, which adjusts the interlayer structure of the product, arranges an inkjet printing layer on the upper and lower sides of the dry particle layer, and sets a special chemical composition of the dry particle layer and the surface glaze layer, so that the product can not only achieve long-term anti-slip without introducing molds or chemical anti-slip agents, but also is not easy to hide dirt and is easy to clean; the product can achieve good color and clarity without post-processing, and has a good simulated three-dimensional effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is a partial schematic diagram of the simulated stone tile prepared in Example 1 of the present invention.

[0043] Figure 2 This is a partial schematic diagram of the simulated stone tile prepared in Comparative Example 9 of the present invention.

[0044] Figure 3 This is a partial schematic diagram of the simulated stone tile prepared in Example 2 of the present invention.

[0045] Figure 4 This is a partial schematic diagram of the simulated stone tile prepared in Comparative Example 7 of the present invention.

[0046] Figure 5 This is a partial schematic diagram of the simulated stone tile prepared in Comparative Example 1 of the present invention.

[0047] Figure 6 This is a partial schematic diagram of the simulated stone tile prepared in Comparative Example 6 of the present invention.

[0048] Figure 7 This is a partial schematic diagram of the simulated stone tile prepared in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0049] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by those of ordinary skill in the art without making creative work premise belong to the protection scope of the present invention. The experimental reagents and instruments involved in the implementation of the present invention, unless otherwise specified, are all commonly used common reagents and instruments.

[0050] Example 1

[0051] An embodiment of a simulated stone tile and a preparation method thereof according to the present invention comprises the following preparation steps:

[0052] (1) a body layer is provided, and then a texture effect pattern is printed on the body layer to provide an effect pattern layer;

[0053] The green body layer comprises the following raw materials in parts by weight:

[0054] 23 parts of potassium and sodium sand, 21 parts of ball clay, 12 parts of kaolin, 7 parts of bentonite, 5 parts of talc, 23 parts of potassium and sodium water abrasive, 3 parts of pyrophyllite, 3 parts of diopside, 3 parts of sodium sand;

[0055] After the raw materials are mixed, they are dried until the moisture content is less than 0.3% and the strength is above 1.8MPa. Then the effect pattern layer is set by printing pattern ink. The printing amount is 5g / m 2 ;

[0056] (2) applying a surface glaze slurry on the effect pattern layer through an electrostatic glaze spraying device to form a surface glaze layer;

[0057] The raw materials for preparing the surface glaze layer include the following components in parts by weight:

[0058] 5 parts of air knife clay, 10 parts of calcined kaolin, 18 parts of potassium feldspar, 22 parts of sodium feldspar, 5 parts of wollastonite, 15 parts of nepheline powder, 3 parts of calcined zinc oxide, 13 parts of zirconium silicate, 13 parts of quartz, 7 parts of calcined alumina, 5 parts of matte frit, 4 parts of dolomite;

[0059] The matte frit comprises the following chemical components in percentage by mass: Al2O3 10.22%, SiO2 50.91%, K2O 4.70%, Na2O 1.22%, CaO 10.11%, ZnO 4.79%, BaO 13.16%, B2O3 2.92%;

[0060] The preparation method of the surface glaze is as follows:

[0061] The raw materials for preparing the surface glaze layers were mixed, and then water (material-water ratio 1:0.4) was added and mixed and ball-milled, and passed through a 325-mesh sieve until the sieve residue was 0.7%, thereby obtaining the surface glaze slurry. The specific gravity of the surface glaze slurry was 1.9 g / mL; the glaze amount of the surface glaze layer was 400 g / m 2 ;

[0062] The chemical composition of the surface glaze layer is shown in Table 1.

[0063] (3) The first inkjet printing layer is set on the surface glaze layer by inkjet printing, and the inkjet printing amount is 2g / m 2 ;

[0064] (4) providing a dry particle layer on the first inkjet printing layer;

[0065] The dry particle layer comprises the following raw materials in parts by weight: 16 parts of potassium feldspar, 40 parts of sodium feldspar, 10 parts of calcined kaolin, 10 parts of barium carbonate, 5 parts of calcined zinc oxide, 4 parts of strontium carbonate, 4 parts of quartz, 6 parts of dolomite, and 5 parts of calcined alumina;

[0066] The chemical composition of the dry granular layer is shown in Table 2.

[0067] The dry particle layer is set by dispensing dry particles;

[0068] The preparation method of the dry granules is:

[0069] The raw materials for preparing the dry particle layer are mixed, then melted at 1500°C and cooled. The obtained sintered mass is crushed and passed through a 300-mesh sieve to obtain dry particles.

[0070] The glaze amount of the dry particle layer is 130g / m 2 .

[0071] (5) Setting a second inkjet printing layer on the dry particle layer by inkjet printing to obtain a rough blank; the inkjet printing amount is 2 g / m 2 ;

[0072] (6) The rough blank is fired at 1180° C. for 60 min, and then polished and edge-ground to obtain the simulated stone tile.

[0073] Example 2

[0074] An embodiment of a simulated stone tile and a preparation method thereof described in the present invention differs from Embodiment 1 only in that the surface glaze layer comprises the following preparation raw materials in parts by weight: 8 parts of air knife clay, 10 parts of calcined kaolin, 17 parts of potassium feldspar, 25 parts of sodium feldspar, 5 parts of wollastonite, 10 parts of nepheline powder, 4 parts of calcined zinc oxide, 10 parts of zirconium silicate, 10 parts of quartz, 11 parts of calcined alumina, 5 parts of matte frit, and 4 parts of dolomite.

[0075] Example 3

[0076] An embodiment of a simulated stone tile and a preparation method thereof described in the present invention differs from Embodiment 1 only in that the surface glaze layer comprises the following preparation raw materials in parts by weight: 8 parts of air knife clay, 10 parts of calcined kaolin, 25 parts of potassium feldspar, 25 parts of sodium feldspar, 5 parts of wollastonite, 5 parts of nepheline powder, 4 parts of calcined zinc oxide, 8 parts of zirconium silicate, 10 parts of quartz, 8 parts of calcined alumina, 8 parts of matte frit, and 4 parts of dolomite.

[0077] Example 4

[0078] An embodiment of a simulated stone tile and a preparation method thereof described in the present invention differs from Embodiment 1 only in that the dry particle layer comprises the following preparation raw materials in parts by weight: 15 parts of potassium feldspar, 45 parts of sodium feldspar, 8 parts of calcined kaolin, 12 parts of barium carbonate, 3 parts of calcined zinc oxide, 6 parts of strontium carbonate, 3 parts of quartz, 6 parts of dolomite, and 3 parts of calcined alumina.

[0079] Example 5

[0080] An embodiment of a simulated stone tile and a preparation method thereof described in the present invention differs from Embodiment 1 only in that the dry particle layer comprises the following preparation raw materials in parts by weight: 18 parts of potassium feldspar, 35 parts of sodium feldspar, 8 parts of calcined kaolin, 11 parts of barium carbonate, 6 parts of calcined zinc oxide, 5 parts of strontium carbonate, 5 parts of quartz, 8 parts of dolomite, and 5 parts of calcined alumina.

[0081] Comparative Example 1

[0082] A simulated stone tile and a preparation method thereof, which differs from Example 1 only in that the dry particle layer includes the following preparation raw materials in parts by weight: 16 parts of potassium feldspar, 10 parts of sodium feldspar, 10 parts of air knife soil, 6 parts of potassium carbonate, 8 parts of calcite, 7 parts of zinc oxide, 5 parts of dolomite, 25 parts of quartz, 3 parts of aluminum oxide, and 10 parts of wollastonite.

[0083] Comparative Example 2

[0084] A simulated stone tile and a preparation method thereof, which differs from Example 1 only in that the surface glaze layer comprises the following preparation raw materials in parts by weight: 20 parts of potassium feldspar, 24 parts of sodium feldspar, 10 parts of air knife clay, 10 parts of calcined kaolin, 8 parts of nepheline powder, 6 parts of calcite, 11 parts of quartz, 10 parts of zirconium silicate, 15 parts of wollastonite, 5 parts of zinc oxide, and 1 part of aluminum oxide.

[0085] Comparative Example 3

[0086] A simulated stone tile and a preparation method thereof, which differs from Example 1 only in that the dry particle layer comprises the following preparation raw materials in parts by weight: 23 parts of potassium feldspar, 16 parts of sodium feldspar, 15 parts of calcined kaolin, 5 parts of barium carbonate, 8 parts of calcite, 5 parts of zinc oxide, 7 parts of strontium carbonate, 9 parts of quartz, 10 parts of wollastonite, and 2 parts of aluminum oxide.

[0087] Comparative Example 4

[0088] A simulated stone tile and a preparation method thereof, which differs from Example 1 only in that the dry particle layer comprises the following preparation raw materials in parts by weight: 19 parts of potassium feldspar, 10 parts of sodium feldspar, 10 parts of calcined kaolin, 6 parts of potassium carbonate, 11 parts of calcite, 3 parts of zinc oxide, 23 parts of quartz, 5 parts of dolomite, 10 parts of wollastonite, and 3 parts of calcined alumina.

[0089] Comparative Example 5

[0090] A simulated stone tile and a preparation method thereof, which differs from Example 1 only in that the surface glaze layer comprises the following preparation raw materials in parts by weight: 10 parts of calcined kaolin, 18 parts of potassium feldspar, 20 parts of sodium feldspar, 5 parts of wollastonite, 15 parts of nepheline powder, 5 parts of calcined zinc oxide, 13 parts of zirconium silicate, 10 parts of quartz, 15 parts of calcined alumina, 5 parts of matte frit, and 4 parts of dolomite.

[0091] Comparative Example 6

[0092] A simulated stone tile and a preparation method thereof, which differs from Example 1 only in that the dry particle layer comprises the following preparation raw materials in parts by weight: 18 parts of potassium feldspar, 40 parts of sodium feldspar, 10 parts of calcined kaolin, 4 parts of barium carbonate, 5 parts of calcined zinc oxide, 10 parts of strontium carbonate, 5 parts of quartz, 6 parts of dolomite, and 2 parts of calcined alumina.

[0093] Comparative Example 7

[0094] A simulated stone tile and a preparation method thereof, the difference from Example 1 is that the dry particle layer comprises the following preparation raw materials in parts by weight: 16 parts of potassium feldspar, 40 parts of sodium feldspar, 10 parts of calcined kaolin, 7 parts of barium carbonate, 5 parts of calcined zinc oxide, 1 part of strontium carbonate, 7 parts of quartz, 9 parts of dolomite, and 5 parts of calcined alumina;

[0095] The surface glaze layer includes the following raw materials in parts by weight: 5 parts of air knife clay, 10 parts of calcined kaolin, 18 parts of potassium feldspar, 27 parts of sodium feldspar, 5 parts of wollastonite, 15 parts of nepheline powder, 3 parts of calcined zinc oxide, 13 parts of zirconium silicate, 8 parts of quartz, 4 parts of calcined aluminum oxide, 8 parts of matte frit, and 4 parts of dolomite.

[0096] Comparative Example 8

[0097] A simulated stone tile and a preparation method thereof, the only difference from Example 1 is that the surface glaze layer includes the following preparation raw materials in parts by weight: 5 parts of air knife clay, 10 parts of calcined kaolin, 18 parts of potassium feldspar, 24 parts of sodium feldspar, 5 parts of wollastonite, 15 parts of nepheline powder, 5 parts of calcined zinc oxide, 13 parts of zirconium silicate, 13 parts of quartz, 3 parts of calcined alumina, 5 parts of matte frit, and 4 parts of dolomite.

[0098] Comparative Example 9

[0099] A simulated stone tile and a preparation method thereof, which differs from Example 1 only in that after applying the dry particle layer, the simulated stone tile is directly fired, then polished and edge-grinded to obtain the simulated stone tile.

[0100] Comparative Example 10

[0101] The only difference between this method and Example 1 is that the dry particle layer and the second printing layer are not applied, and other conditions remain unchanged. The product surface is cleaned, and commercially available anti-slip powder and water are mixed in a mass ratio of 1:1 to prepare an anti-slip agent, and then a layer of the anti-slip agent is evenly brushed on the product surface.

[0102] In addition, the surface glaze layer and dry particle layer described in Table 1 and Table 2 also contain inevitable trace impurities or loss on ignition, which are not listed here one by one.

[0103] Table 1

[0104]

[0105] Table 2

[0106]

[0107]

[0108] Effect Example 1

[0109] In order to verify the use effect of the simulated stone tiles of the present invention, the products prepared in the embodiments and comparative examples were subjected to the following tests:

[0110] (1) Anti-slip test: Test the anti-slip level according to the DIN51130.14 standard tilt platform method;

[0111] (2) Stain resistance test: Test the stain resistance level according to GB / T3810.14 standard;

[0112] (3) Grain evaluation test: select 10 testers, use marble as a control, and evaluate the surface grain of each product under reflected light. The score is 1 to 10 (integer points). The clearer the grain, the higher the score. The average score of each sample is calculated and recorded;

[0113] (4) Cleanability test: Use an oil-based pen to draw on the product surface, then wipe it with a damp cloth to check if there are any marks left.

[0114] The test results are shown in Table 3.

[0115] Table 3

[0116]

[0117]

[0118] It can be seen from Table 3 that the simulated stone tiles prepared in each embodiment have an ideal use effect. In terms of anti-slip effect, the anti-slip level can reach R10 or above; at the same time, in terms of anti-fouling, the test results of the products under different anti-fouling system tests are all level 5; in terms of cleanability test, after being painted with an oily pen, each product can be directly wiped clean with a wet rag without leaving any traces. In terms of appearance effect, the product is based on the full integration and positioning of the inkjet printing layer, the surface glaze layer and the dry particle layer, and the texture is clear and three-dimensional, such as Figure 1 and 3 As shown, the scores all reached 8.5 points or above. Among them, based on the optimization of the dry particle layer and the surface glaze layer components, the comprehensive performance of the product in Example 1 is better.

[0119] In contrast, due to improper composition of the dry particle layer and the surface glaze layer, the products obtained in Comparative Examples 1 to 8 are basically unable to achieve the same effect as the products in the examples. The main reason is that under inappropriate composition, when the dry particle layer and the surface glaze layer are not introduced with anti-slip agent or mold process, the number of pinhole defects in the dry particle layer may not be controlled, and the particle size is also large, resulting in the product being unable to take into account both anti-fouling and easy-to-clean properties, and the texture effect is also poor. Figure 1 and Figure 5 , Figure 6 , Figure 7 As shown in the figure, due to improper selection of raw materials for the preparation of the dry particle layer, improper setting of the silicon-aluminum ratio of the dry particle layer in the products of Comparative Examples 1, 6 and 4, improper setting of the sodium-potassium content, improper setting of the contents of the metal oxides barium oxide, zinc oxide, calcium oxide and magnesium oxide, the three products not only cannot guarantee the anti-skid and anti-fouling properties, but also the local appearance texture is not clear and not three-dimensional under reflection; and the improper setting of the surface glaze layer not only affects the appearance texture effect, but also affects the anti-skid and anti-fouling properties of the product due to its close connection with the printing layer and the dry particle layer, as shown in Comparative Examples 2, 5, 7 and 8, while Figure 4 It can be seen from the corresponding comparative example 7 that when the surface glaze layer is not properly set, the local texture of the product will also become very blurred and unclear.

[0120] The product described in Comparative Example 9 does not have a second inkjet printing layer after the dry particle layer is applied. A direct comparison is made on the same part of the product in Example 1. Figure 2 As shown, it can be clearly seen that the texture clarity and three-dimensionality have decreased, and the anti-skid performance and anti-fouling performance have also decreased compared with the product in Example 1, which fully demonstrates that the setting of the second inkjet layer also has a certain impact on the performance of the product. The product described in Comparative Example 10 uses traditional technology, and an anti-skid agent is set on the product surface instead of a dry particle layer. It can be seen that the performance and appearance of this product are not as good as the product of the present invention.

[0121] Subsequently, the product bricks obtained in Example 1 and Comparative Example 10 were placed face up on the floor of a company's punch card machine to simulate use for more than 10,000 times in one month, and then tested by static friction method and pendulum method wet BPN. The test was based on the anti-slip grade test of GB / T35153-2017 standard. The results are shown in Table 4.

[0122] Table 4

[0123]

[0124] It can be seen from the test results that the anti-slip performance of the product of Comparative Example 10 prepared by the traditional process declines after a period of use, and the anti-slip property is not durable, while the product of Example 1 still maintains the initial anti-slip level and has strong durability.

[0125] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, the present invention is still applicable to those skilled in the art. Figure 1 This is the simulated stone tile picture of Example 1. Figure 2 As can be seen from the picture of comparative example 9, the clarity of the simulated marble without printing the second printing layer is obviously lower than the ceramic tile of the invention. Ordinary technicians should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A simulated stone tile, characterized in that: It comprises a surface glaze layer, a first inkjet printing layer, a dry particle layer and a second inkjet printing layer which are adjacent to each other in sequence; The surface glaze layer comprises the following chemical components in percentage by mass: Al2O3 19.56-25.12%, SiO2 49.14-56.5%, K2O 2.11-3.05%, Na2O 2.89-4.05%, CaO 2.12-3.75%, ZrO2 4.54-7.65%, MgO 0.97-1.85%, ZnO 2.16-4.45%, BaO 0.19-1%; The dry particle layer comprises the following chemical components in percentage by mass: Al2O3 16.56-20.12%, SiO2 47.14-52.51%, K2O 1.31-2.61%, Na2O 3.89-5.05%, CaO 2.05-4.88%, SrO 2.54-4.65%, MgO 1.02-1.85%, ZnO 3.16-5.45%, and BaO 8.41-12.10%.

2. The simulated stone tile according to claim 1, characterized in that: The surface glaze layer comprises the following raw materials in parts by weight: 5-15 parts of air knife clay, 5-15 parts of calcined kaolin, 15-30 parts of potassium feldspar, 15-30 parts of sodium feldspar, 5-9 parts of wollastonite, 5-15 parts of nepheline powder, 3-8 parts of calcined zinc oxide, 5-15 parts of zirconium silicate, 5-15 parts of quartz, 7-12 parts of calcined aluminum oxide, 5-10 parts of matte frit, and 3-5 parts of dolomite; The matte frit comprises the following chemical components in percentage by mass: Al2O3 10.14-15.12%, SiO2 50.14-55.68%, K2O 4.15-5.04%, Na2O 1.04-1.85%, CaO 8.12-10.18%, ZnO 4.01-5.45%, BaO 10.56-13.16%, and B2O3 1.98-3.54%.

3. The simulated stone tile according to claim 1, characterized in that: The dry particle layer comprises the following raw materials in parts by weight: 15-25 parts of potassium feldspar, 35-45 parts of sodium feldspar, 5-10 parts of calcined kaolin, 8-12 parts of barium carbonate, 3-6 parts of calcined zinc oxide, 3-7 parts of strontium carbonate, 1-5 parts of quartz, 5-10 parts of dolomite and 3-8 parts of calcined aluminum oxide.

4. The simulated stone tile according to claim 1, characterized in that: The dry particle layer comprises the following chemical components in percentage by mass: Al2O3 18-19%, SiO2 49.5-50.5%, K2O 1.7-1.8%, Na2O 4.1-4.5%, CaO 2-2.5%, SrO 2.9-3%, MgO 1.4-1.5%, ZnO 5-5.2%, and BaO 10-10.5%.

5. The simulated stone tile according to claim 1, characterized in that: The simulated stone tile also includes a body layer and an effect pattern layer arranged on the body layer.

6. The method for preparing the simulated stone tile according to any one of claims 1 to 5, characterized in that: The following steps are involved: Setting a body layer, then printing a texture effect pattern on the body layer, and setting an effect pattern layer; A surface glaze layer is provided on the effect pattern layer; Providing a first inkjet printing layer on the surface glaze layer by inkjet printing; Disposing a dry particle layer on the first inkjet printing layer; Arranging a second inkjet printing layer on the dry particle layer by inkjet printing to obtain a rough blank; The rough blank is fired, and then polished and edge-ground to obtain the simulated stone tile.

7. The method for preparing the simulated stone tile according to claim 6, characterized in that: The dry particle layer is set by dispensing dry particles.

8. The method for preparing the simulated stone tile according to claim 6, characterized in that: The surface glaze layer is provided by applying the surface glaze slurry; the preparation method of the surface glaze is as follows: The raw materials for preparing each surface glaze layer are mixed, then water is added, mixed and ball-milled, and sieved to obtain the surface glaze slurry.

9. The method for preparing the simulated stone tile according to claim 6, characterized in that: The glaze amount of the dry particle layer is 100-150 g / m 2 The glaze amount of the surface glaze layer is 350-450g / m 2 .

10. The method for preparing the simulated stone tile according to claim 6, characterized in that: The firing temperature is 1150-1200° C., and the firing time is 50-80 minutes.

Citation Information

Patent Citations

  • Full-body porcelain brick having inkjet effect, and preparation method thereof

    CN109553299A

  • Colored seeding glaze, and positioning crystal pattern ceramic tile prepared using same

    CN110746117A

  • Dry-particle inkjet stone-like brick with whole-body effect and preparation method thereof

    CN111574228A

  • Simulation marble glaze, simulation marble large board and preparation method

    CN113860742A

  • Ceramic tile and preparation method thereof

    CN115028476A